2018
DOI: 10.1002/mrm.27482
|View full text |Cite
|
Sign up to set email alerts
|

3D high‐resolution imaging of 2‐hydroxyglutarate in glioma patients using DRAG‐EPSI at 3T in vivo

Abstract: Purpose To develop 3D high‐resolution imaging of 2‐hydroxyglutarate (2HG) at 3T in vivo. Methods Echo‐planar spectroscopic imaging with dual‐readout alternated‐gradients (DRAG‐EPSI), which was recently reported for 2D imaging of 2HG at 7T, was tested for 3D imaging of 2HG at 3T. The frequency drifts and acoustic noise induced by DRAG‐EPSI were investigated in comparison with conventional EPSI. Four patients with IDH‐mutant gliomas were enrolled for 3D imaging of 2HG and other metabolites. A previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Implementation of 2HG measurement for volumetric acquisitions has also been demonstrated (Figure 2). 54,57,58 …”
Section: Clinical Utility Of Mrsi Of the Brainmentioning
confidence: 99%
“…Implementation of 2HG measurement for volumetric acquisitions has also been demonstrated (Figure 2). 54,57,58 …”
Section: Clinical Utility Of Mrsi Of the Brainmentioning
confidence: 99%
“…As for pre-operative molecular diagnosis of gliomas, IDH mutation can be well recognized by identification of 2-HG on 7.0 Tesla magnetic resonance spectroscopy (MRS) [ 10 ]. Other sequences on MR, like dual phase recognition alternating gradient (DRAG)-plane echo spectrum imaging (EPSI), has also been tried to distinguish 2-HG, as 3D imaging on DRAG-EPSI produces a frequency shift 5.5 times smaller and reduce noise by 25 dB compared with conventional method [ 11 ]. It has also been reported that IDH mutation can be predicted by radiomics, or deep learning-based radiomics (DLR) from multiple modalities of MR images by convolutional neural network [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic FDG-PET was used to describe IDH1 genotype in gliomas [19,20]. PET images could reveal metabolic differences among gliomas, providing a possible non-invasive preoperative molecular diagnosis with FDG, 11 C-choline(CHO), or 11 C-methionine(MET) [21,22]. MET-PET/MRI has been reported to predict the IDH mutation of gliomas, by calculating the maximum tumor-brain ratio of MET uptake, and the receiver operating characteristic (ROC) analysis showed high AUC of 0.79 [23].…”
Section: Introductionmentioning
confidence: 99%
“…wt, wild-type. 4 JEŽ EK Phosphoglycerate dehydrogenase. Also, human phosphoglycerate dehydrogenase (PHGDH; EC 1.1.1.95) has been reported to form r-2HG from 2OG (47).…”
Section: Fig 2 Dimeric Structure Of Idh2 (A)mentioning
confidence: 99%
“…Typically, millimolar concentrations of 2HG are found in gliomas bearing IDH1/2 mutants ( Table 1 ). In vivo magnetic resonance (MR) imaging using echo-planar spectroscopic imaging dual-readout alternative gradients (DRAG-EPSI) detected 5 m M 2HG before surgery and 3–6 m M after surgery ( 4 ). Similar concentrations were found using long echo time MR spectroscopy with semi-localization by adiabatic selective refocusing.…”
Section: Hg As An Oncometabolitementioning
confidence: 99%